SINERGI PERAN GEREJA DAN KELUARGA DALAM MENGHADAPI PHUBBING SERTA KECANDUAN GADGET PADA GENERASI ALPHA DI ERA DISRUPSI - Irene Christanti Hutabarat; Roni Kurniawan; Yosef Antonius (Sekolah Tinggi Teologi Arastamar Bengkulu, 2026)
The era of digital disruption poses serious challenges to the formation of faith and character in Generation Alpha, who have been familiar with technology since birth. Gadgets and the internet, which initially served as tools for education and communication, have now often become sources of dependence, affecting their social and spiritual interaction patterns. Similarly, the widespread phenomenon of Phubbing, which is the act of ignoring real relationships in favour of virtual interactions,is evidence that gadget addiction not only damages communication between peers but also erodes the quality of family relationships and the spiritual life of the alpha generation. The purpose of this study is to examine the integration of the roles of the church and family in dealing with Phubbing and gadget addiction among Generation Alpha. Using a qualitative method with a literature study approach, it can be concluded that Phubbing and gadget addiction are serious phenomena that threaten the quality of Generation Alpha's social and spiritual relationships, so that the church is called to be present as a koinonia community that strengthens spirituality amid the tide of disruption. The family, as the basis of Christian faith and character education, has the primary responsibility for shaping a balanced spiritual habitus and digital ethics. The integration of the roles of the church and family in facing these challenges has significant practical theological implications for the character formation of Generation Alpha so that they remain rooted in the Christian faith while being adaptive to the digital age.